(untitled) (Al-Qamar, 2024)
Allah tala reviled a sacred book the holy Quran in consecutively into prophet PBUH without doubt. Quran leads humankind in every aspect of life it is claimed in Holly Quran and every claimed need reference. Different tafaseer of Quran claim of references, because human being objective is to spare his life according to Islam. Every spare of life Muslims with accordance to take benefits from tafaseer. Indo Pak Muslim not remained behind they showed their love in different ways, on this, The Qalam e elahi is on the surface because indo Pak Muslim language is Urdu. For this sake, a large number of tafaseer written in Urdu language. In Urdu language tafaseer Bayan ul Quran and tafseer e Naeemi retain fame. In these both obligation fiqh has been taken from Hanafi in tafaseer, both mufasreen also belonged to Hanafi sect instead of this, is difference between their opinions require attention